MODELI NG CLINICAL AND ECONOMIC OUTCOMES OF TESTING FOR LTBI WITH T-SPOT.TB IN IMMUNOCOMPROMISED CHILDREN - V. I. Ignatyeva; M. V. Avxentyeva; V. V. Omelyanovsky; G. R. Khachatryan (Фармакоэкономика, 2015)
weakening of immune status under the influence of some diseases or types of treatment could result in the activation of the present latent tuberculosis infection (LTBI). Recently it was suggested to use the immunoenzymometric interferon-gamma tests, T-SPOT.TB among them, but their costs are substantially higher than cost of the traditionally used tuberculin skin test (TST), thus the need for efficiency assessment arises. The aim of the study was to evaluate the cl inical and economic outcomes of testingfor LTBI with T-SPOT.TB in immunocompromised children. Methods: we develope d a model, forecasting the testing results, probable cases of tuberculosis activation and related costs for scenarios with alternative use of T-SPOT.TB and TST for diagnosing LTBI in immunocompromised children. Parameters for mo deling were derived from published data on sensitivity and specificity of tests and prevalence of LTBI in Russia. Costs were estimated from the position of overall government budget and included costs ofprim ary LTBI testing, additional testing to exclude active tuberculosis in case of positive result, preventive chemotherapy and costs of treatment for cases of tuberculosis activation. Results: there would be 20 tr ue positive and 80 true negative tests in the cohort of 100 patients if the test's sensivity and specificity were 100% and prevalence of LTBI was 20%. When testing with TST 100 immunocompromised children we expected that there would be 40 positi ve tests (among them 7 true positive, meaning that only 7 out of20 children with LTBI would be found in the developed model), and 3 cases of tuberculosis activation. When using T-SPOT.TB in the same cohort there were 19 positive tests in the developed model (14 out of 20 LTBI cases detected), tuberculosis activation was possible in 2 cases. The total costs per cohort were 1.71 mln RUR. in case of TST testing (including primary testing costs – 7,900 RUR) and 1.07 mln RUR for scenario with T-SPOT.TB testing (including primary testing costs – 250,000 RUR). Conclusions: The use of T-SPOT.TB for LTBI detection in immunocompromised children is efficient, as additional costs for primary testing could be compensated by the following decrease of costs related to additional testing and preventive chemotherapy.